-3(2y-4)=-6

Simple and best practice solution for -3(2y-4)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2y-4)=-6 equation:


Simplifying
-3(2y + -4) = -6

Reorder the terms:
-3(-4 + 2y) = -6
(-4 * -3 + 2y * -3) = -6
(12 + -6y) = -6

Solving
12 + -6y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -6y = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -6y = -6 + -12
-6y = -6 + -12

Combine like terms: -6 + -12 = -18
-6y = -18

Divide each side by '-6'.
y = 3

Simplifying
y = 3

See similar equations:

| -9x+5x-4x=0 | | 3x+8=x+18 | | 49t^2+147t=0 | | -15=x | | 46=-x | | 5x+5y= | | -x=96 | | F=10(x-70)+50 | | 3a-30=-4 | | 0.6(x+7)=24 | | -4=x^3+3x^2-9x-13 | | 3(2y-4)=5(y+3) | | -5=x^3+3x^2-9x-13 | | -4-(-3)= | | -110+22x=-1 | | 3x^2+15x-2=0 | | -16t^2+32t+32=0 | | -8+2x=6 | | -132+11x=-3 | | 4x-10x=36 | | -y+3x+6=-5 | | 3p-2=29 | | 41k=-2747 | | 9y+4y=104 | | 5x+-6=11 | | 29+n=13 | | 4x-9=-9 | | 4a-5=15 | | X-7=-19 | | 5x=4y+28 | | 2(2y-4)=3(y+5) | | 0.4(x-9)=20 |

Equations solver categories